The Influence of Neighboring Base Pairs upon Base-Pair Substitution Mutation Rates - Koch, Robert E. (1971)
The 2-aminopurine-induced transition, A·T → G·C, was studied at particular sites in bacteriophage T4 as a function of the nearby base-pair composition of the DNA. Changing a base pair changed the transition rate at the adjacent base pair up to 23-fold, and at the next base pair by a lesser amount. Destabilization was achieved by replacing an A·T base pair by a G·C base pair.